2008
DOI: 10.1055/s-0028-1087177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metformin on the Incidence of Type 2 Diabetes Mellitus and Cardiovascular Disease Risk Factors in Overweight and Obese Subjects – The Carmos Study

Abstract: Metformin reduces the occurrence of T (2)DM in overweight and obese non-diabetic adults and decreases the rate of MetS by improving the CVD risk factor profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 20 publications
3
40
2
Order By: Relevance
“…In another type 2 model, db/db mice, rapamycin treatment improved diabetic renal hypertrophy [99]. Metformin has also been used successfully in the prevention of type 2 diabetes in patients with metabolic syndrome [100].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…In another type 2 model, db/db mice, rapamycin treatment improved diabetic renal hypertrophy [99]. Metformin has also been used successfully in the prevention of type 2 diabetes in patients with metabolic syndrome [100].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…20). Metabolic syndrome Z-scores and ATP III criteria were calculated to describe the efficacy of each treatment on metabolic syndrome severity and total number of risk factors (18). Sex specific Z-scores were calculated as: male Z-score ¼ ((40ÀHDL)/10.7) þ ((TAGÀ 150/88.5)) þ ((FPGÀ100)/11.9) þ ((WCÀ102)/14.3) þ ((MAPÀ 100)/8.8), and female Z-score ¼ ((50ÀHDL)/11.0) þ ((TAGÀ150/ 88.5)) þ ((FPGÀ100)/11.9) þ ((WCÀ88)/13.6) þ ((MAPÀ100)/ 8.8).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Cardiac pulsatility and aortic compliance may result in aortic annulus changes [3]. However, the dynamic changes of aortic annulus during the cardiac cycle have not been clarified in patients with aortic stenosis (AS) [4][5][6]. Knowledge of the dynamic characteristics of aortic annulus in this population may improve our understanding of aortic annulus and help accurately size aortic annulus.…”
mentioning
confidence: 98%
“…Several studies have shown that a reduction in endothelial function [2] may represent the link between IR and decline in cardiovascular performance. Treatment with metformin has been reported to prevent the above-mentioned cardiac abnormalities [3] and the evolution of IR diabetes [4]. However, metformin has also been shown to slightly but significantly reduce oxygen consumption in a population of healthy individuals [5].…”
mentioning
confidence: 99%